2020
DOI: 10.1051/0004-6361/202038212
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary study of complex organic molecules in high-mass star-forming regions

Abstract: We have studied four complex organic molecules (COMs), the oxygen-bearing methyl formate (CH3OCHO) and dimethyl ether (CH3OCH3) as well as the nitrogen-bearing formamide (NH2CHO) and ethyl cyanide (C2H5CN), towards a large sample of 39 high-mass star-forming regions representing different evolutionary stages, from early to evolved phases. We aim to identify potential correlations and chemical links between the molecules and to trace their evolutionary sequence through the star formation process. We analysed sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 156 publications
3
24
0
Order By: Relevance
“…The enhancement of COMs in low-mass Class 0 and Class I protostars is illustrated in Figure 12, and is a trend that has been seen before (e.g., López-Sepulcre et al (2017)). In a process laid out recently by Coletta et al (2020), who observed this same trend in a large sample of massive star-forming regions, molecular abundance will increase through thermal or shock induced desorption of COMs, first formed on ices.…”
Section: )mentioning
confidence: 59%
“…The enhancement of COMs in low-mass Class 0 and Class I protostars is illustrated in Figure 12, and is a trend that has been seen before (e.g., López-Sepulcre et al (2017)). In a process laid out recently by Coletta et al (2020), who observed this same trend in a large sample of massive star-forming regions, molecular abundance will increase through thermal or shock induced desorption of COMs, first formed on ices.…”
Section: )mentioning
confidence: 59%
“…However, the mean values of observed abundances show an increase of one order of magnitude among HMSCs and more evolved sources, but no clear distinction between HMPOs and UC HII regions in the TOPGöt sample. An increase in abundances with evolutionary stages has been found by Coletta et al (2020) for other COMS such as methyl formate, dimethyl ether and ethyl cyanide, and it is a powerful tool to infer the evolutionary stage of a source without performing a multi-wavelength analysis. -From the comparison of values of X CH 3 CN in already classified sources of the Sub-sample I, we found five good candidates of HMSCs or very early HMPOs in Sub-sample II.…”
Section: Discussionmentioning
confidence: 98%
“…A small part of the observations towards these sources has already been analyzed and published in previous works covering different topics, from deuteration in selected molecules (N 2 H + , CH 3 OH, NH 3 , HC 3 N; Fontani et al 2011Fontani et al , 2015aRivilla et al 2020), to nitrogen fractionation of HCN, HNC and N 2 H + (Fontani et al 2015b;Colzi et al 2018a), to prebiotic and complex organic molecules (COMs, Mininni et al 2018;Coletta et al 2020).…”
Section: Selection Criteria For Hmpos and Uc Hii Regionsmentioning
confidence: 99%
“…There are well-known hot cores in the molecular clouds of Sgr B2 and Orion [71][72][73][74][75] while IRAS 16293-2422, NGC1333 IRAS2A, IRAS4A and IRAS4B were the first discovered hot corinos. 14,58,[76][77][78] With low mass protostars, there is also evidence for sublimation fronts. For instance, the sublimation radius for the more volatile CO is observed to be located at larger radii than that of water and other more complex species 79,80 .…”
Section: Excitation Temperaturesmentioning
confidence: 99%